Penataan Penjadwalan Preventive Maintenance Semua Mesin Milling Wheat Menggunakan Metode TPM (Total Productive Maintenance) - Wicaksono, Bagus; Hatta, Mochammad; Nurmawati, Nurmawati; Kusnawati, Ida (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
PT X is a factory that processes wheat into flour with roll mill as the main equipment. The wheat used is a blend of Indian wheat and Australian wheat. Indian wheat has a hard texture that can cause the roll grinding to become damaged or dull, increased working amperes,bearing jams, broken belts and motor overload which causes downtime. When a machine or component breaks down, the production process in the company will be disrupted and may come to a halt, so the target is not achieved and endangers to the company. To keep production machines and equipment working, maintenance processes are carried out properly and regularly. Additionally, the company can implement preventive maintenance steps to prevent and reduce machine downtime. Preventive maintenance is a planned maintenance strategy to prevent potential breakdowns. To reduce the high machine downtime, preventive maintenance is solution . The method chosen in this research is Total productive Maintenance. Based on research results, the overall equipment effectiveness (OEE) values were 85.8% in January, 87.18% in May, 86.69% in June, 85.25% in November, and 85.51% in December. The OEE values that did not meet the standard occurred in February (81.92%), March (81.34%), April (84.73%), July (83.77%), August (79.03%), September (77.05%), and October (81.72%). The biggest factor that causing losses of overall equipment effectiveness is caused by the high value of the six big losses, particularly the reduced speed losses, which stand at 9%.